Seroprevalence and risk factors for Rift Valley fever and Capripoxvirus in small ruminants in the border region of Tanzania - Zambia - Olovsson, Emelie (2019)
Tanzania is a country where poverty is still high and many households are dependent on agriculture to support their families. Small ruminants, such as sheep and goats, make up an important part of agriculture; they are cheap to buy and can easily be sold or exchanged for the farmers. The animals therefore function as a living bank and should unforeseen expenses arise, the money can be made available by selling an animal. This means that the health of these animals is important socio-economically for the farmers.